Connection Management Self-Concept and Social Support With Student Confidence - Lahmuddin Lubis; Abdurrahman .; Elsa Fazira (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This article aims to empirically examine the relationship between self-concept and social support with the self-confidence of the students of MTsS Al-Washliyah Tembung. The population in this study amounted to 246 students with a sample of 105 students. The sampling technique in this study used a purposive sampling technique. The results showed that, an instrument used to obtain the data is the self-confidence scale, self-concept scale, and social support scale. The results of data analysis using regression analysis obtained the regression coefficient of the three variables of 0.679 (p <0.01) this means that there is a significant relationship between self-concept and social support with student self-confidence so that the hypothesis proposed in this study is accepted. The effective contribution of self-concept and social support variables with student self-confidence is 67%. The correlation coefficient between the variables of self-concept and students' self-confidence is 0.6555 (p<0.01). This means that there is a significant positive relationship between self-concept and students' self-confidence. While the correlation coefficient between the variables of social support and students' self-confidence is 0.437 (p < 0.01) this means that there is a significant positive relationship between social support and student self-confidence, so the hypothesis proposed in the study is accepted. This means that there is a significant positive relationship between self-concept and students' self-confidence. While the correlation coefficient between the variables of social support and students' self-confidence is 0.437 (p < 0.01) this means that there is a significant positive relationship between social support and student self-confidence, so the hypothesis proposed in the study is accepted. This means that there is a significant positive relationship between self-concept and students' self-confidence. While the correlation coefficient between the variables of social support and students' self-confidence is 0.437 (p < 0.01) this means that there is a significant positive relationship between social support and student self-confidence, so the hypothesis proposed in the study is accepted.